PENGARUH IMPLEMENTASI KEBIJAKAN, PRESEPSI DAN EFEKTIFITAS TERHADAP KEPUASAN MASYARAKAT PENERIMA BANTUAN LANGSUNG TUNAI DANA DESA (BLT Dana Desa) NAGARI KOTO SALAK TAHUN 2020 - Kelik Purwanto; May Roza Wiska; Tri Okta Hidayani (Nusantara Hasana Journal, 2022)
At the end of 2019, the world was shocked by the Covid-19 virus which affected the people’s economy. The government prepares assistance sourced from APBN funds and then launched through Village Funds throughout Indonesia, especially Nagari Koto Salak, as explained by the Nagari Koto Salak government that those who are entitled to assistance are the elderly and single parents. In fact, the policies implemented have not been maximized because there are still elderly names who have not been registered for assistance. In this way, the effectiveness of community satisfaction is reduced because the Permendes Year 2020 Number 6 policies that have been issued have not been implemented properly and the officers are less collective when determining the recipients of the assistance. the satisfaction of the recipients of BLT DD Nagari Koto Salak. This research is a quantitative type using primary data. Data was collected by using the questionnaire method. The population in this study amounted to 164 recipients of BLT DD Nagari Koto Salak in 2020. The analysis technique used was multiple regression. The results of this study indicate that there is a simultaneous (together) significant effect between policy implementation, perception and effectiveness on the satisfaction of the community receiving BLT Dana Desa with a value of fhitung = 3,809 > nilai ftabel = 2,43 with asignificant value of 0,011. To the government, it is recommended that in the process of implementing the distribution of BLT Village funds, it is better to reduce errors in data collection so that it is right on target by applying a systematic survey method.